Adventure in the Age of COVID-19: Embracing Microadventures and Locavism in a Post-Pandemic World. (9th July 2020) - Mackenzie, Susan Houge; Goodnow, Jasmine
Abstract: Unprecedented mobility restrictions due to COVID-19 have frozen the adventure travel and tourism industry. These restrictions have forced many to embrace 'hyperlocal' approaches to adventure and provided an opportunity to reimagine our adventure travel philosophies and practices. Despite claims that traditional adventure travel could address some of the "world's most pressing challenges", it has largely failed to realize its potential to provide a range of social, economic, and environmental benefits. Conversely, microadventure, which espouses adventures in nearby nature that are low-carbon and human-scaled, is an enticing alternative for both current and post-pandemic conditions. This essay first critiques pre-pandemic adventure travel and describes the hazards of this approach in age of COVID-19. It then explores creative 'lockdown' microadventures; envisions what post-pandemic adventure may look like; and explains why we not only need to embrace microadventures in a post-pandemic world, but also why we may prefer them to traditional adventure travel.